Apakah Indeks Pembangunan Manusia dan Hotel Mempengaruhi Disparitas Pendapatan ? - Amrullah, Muhammad; Wahyudi, Setyo Tri; Ekawaty, Marlina (Jurnal Ekonomi Kuantitatif Terapan, 2020)
Progress in the tourism sector does not always have a good effect on the distribution of income between regions. This happened in Bali Province which had progress in the tourism sector but apparently had problems in the form of unequal distribution of income between regions that have well-known tourism objects and areas without well-known tourist attractions. This study uses the fixed effect panel data method in the form of cross section data covering 9 districts/cities and time series data covering data for the period 2008 to 2018. This study aims to determine the effect of the tourism sector and the human development index on inequality distribution income in the Province of Bali.  The results of this study found that overall, the number of hotels and the human development index had a significant effect on the inequality of income distribution. The number of hotels has no significant effect on the disparity in income distribution, while the human development index has a positive and significant effect on the income distribution inequality. Meanwhile, the influence of the Interaction Variable between the Number of Hotels and the Human Development Index obtained an insignificant influence on the income disparity in the Province of Bali.